1994
DOI: 10.1152/jappl.1994.77.3.1542
|View full text |Cite
|
Sign up to set email alerts
|

Prior exercise suppresses the plasma tumor necrosis factor response to bacterial lipopolysaccharide

Abstract: This study was initiated to determine the effect of physical exercise on the in vivo tumor necrosis factor-alpha (TNF) response to Escherichia coli lipopolysaccharide (LPS). Rats familiarized with treadmill running and surgically implanted with vascular catheters were either not exercised or exercised to near exhaustion (mean run time of 102 +/- 13 min) before intravenous LPS challenge (1 mg/kg; lethality of dose is 10-20% in 24 h). Compared with time-matched nonexercised control rats, exercised rats had incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 0 publications
3
31
2
2
Order By: Relevance
“…6). This phenomenon, that pathogen-induced increases in plasma TNF-α concentrations are attenuated by prior exhaustive exercise, seems to be similar to that of LPS-induced TNF-α responses in plasma 35,36,60) . Therefore, intense exercise inhibits poly I:C, R-848 and CpG DNAinduced pro-inflammatory cytokine production, which might increase the risk of infection with viruses (Fig.…”
Section: Strenuous Exercise-induced Tnf-α Suppression In Response To supporting
confidence: 51%
See 3 more Smart Citations
“…6). This phenomenon, that pathogen-induced increases in plasma TNF-α concentrations are attenuated by prior exhaustive exercise, seems to be similar to that of LPS-induced TNF-α responses in plasma 35,36,60) . Therefore, intense exercise inhibits poly I:C, R-848 and CpG DNAinduced pro-inflammatory cytokine production, which might increase the risk of infection with viruses (Fig.…”
Section: Strenuous Exercise-induced Tnf-α Suppression In Response To supporting
confidence: 51%
“…Additionally, Bagby et al reported that corticosterone concentrations are increased in rats immediately after exhaustive exercise. However, the corticosterone levels also increase to similar concentrations in rats that do not exercise after an LPS challenge 35) . Therefore, exhaustive exercise-induced corticosterone activity does not affect the TNF-α response to LPS.…”
Section: Biological Mechanisms Underlying Strenuous Exerciseinduced Tmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, Bagby et al [12] reported that stressful exercise reduced the production of the proinflammatory cytokine TNF-␣ in response to LPS, a component of the cell wall of gram-negative bacteria. TNF-␣ production by LPS-activated macrophages is a major mediator of many of the effects of LPS in vivo [13] .…”
mentioning
confidence: 99%